2004
DOI: 10.1111/j.1365-3180.2004.00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selected pesticides and adjuvants on germination and vegetative growth of Phomopsis amaranthicola, a biocontrol agent for Amaranthus spp.

Abstract: Summary Phomopsis amaranthicola, a bioherbicide agent for Amaranthus spp., was tested in vitro for its compatibility with commercial formulations of 16 adjuvants, 24 herbicides, nine fungicides and four insecticides at 2X, 1X (highest labelled product dose rate), 0.75X, 0.5X and 0.25X concentrations. These chemicals were tested for their effects on spore germination. Selected herbicides and fungicides at 1X were also tested for their influence on colony growth and sporulation. All tested compounds were finall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 24 publications
2
33
1
2
Order By: Relevance
“…22) As abamectin, fenpropathrin, and thiamethoxam had a moderate inhibitory e ect, their eld application may be combined with that of C. rosea. Malathion was the most toxic to C. rosea, as found with Phomopsis amaranthicola 14) and Paecilomyces fumosoroseus. 15) e active ingredient of malathion has no antifungal activity; its e ect may be more related to the inert compounds in the formulation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…22) As abamectin, fenpropathrin, and thiamethoxam had a moderate inhibitory e ect, their eld application may be combined with that of C. rosea. Malathion was the most toxic to C. rosea, as found with Phomopsis amaranthicola 14) and Paecilomyces fumosoroseus. 15) e active ingredient of malathion has no antifungal activity; its e ect may be more related to the inert compounds in the formulation.…”
Section: Discussionmentioning
confidence: 95%
“…8,12,13) Both growth and germination were reduced by the fungicides; growth was more a ected than germination. A pesticide may di erentially a ect spore germination and mycelial growth 14) and these e ects may vary according to the fungal species. 15,16) It is worth considering what process, conidial germination or mycelial growth, is more hindered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports of both enhanced and reduced disease severity have been published and glyphosate seem to have preventative and curative properties. Furthermore, the formulation and adjuvants used to enhance the efficiency of the active compound can dramatically affect germination, growth, and propagation of fungal plant pathogens (Smith & Hallett, 2006;Weaver et al, 2006;Weaver, et al, 2009;Wyss et al, 2004). Interestingly, glyphosate has also been reported to www.intechopen.com control mammalian pathogenic fungi (Nosanschuk et al, 2001) and was active against apicomplexan parasites that cause diseases such as malaria and toxoplasmosis (Roberts et al, 2002).…”
Section: Glyphosatementioning
confidence: 99%
“…These results suggest that timing of glyphosate application in relation to combined treatment with a bioherbicide is important. Wyss et al (2004) reported that certain pesticides and their adjuvants affected spore germination and growth of Phomopsis amaranthicola, an effective bioherbicides against Amaranthus species. Several herbicides such as glyphosate had also negative effects on spore germination of P. setariae (Peng & Byer, 2005).…”
Section: Leaf Pathogensmentioning
confidence: 99%